2012
DOI: 10.1210/jc.2011-3290
|View full text |Cite
|
Sign up to set email alerts
|

Possible Role of Adrenomedullin In the Pathogenesis of Tubal Ectopic Pregnancy

Abstract: Context: Tubal ectopic pregnancy (tEP) is currently the leading cause of pregnancy-related deaths during the first trimester. Our current knowledge on the molecular pathogenesis is limited. Objective:The objective of the study was to find out the possible role of adrenomedullin (ADM) in the pathogenesis of tEP. Design:This was an experimental in vitro study on oviductal tissue. Setting:The study was conducted at a university teaching hospital. Patients and Interventions:Patients included those having oviducts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…Stimulating effects of ADM is blocked by the calcitonin-gene-related peptide (CGRP) receptor antagonist [53]. In line with these studies, it has been suggested that plasma and tubal levels of ADM are lower in patients with tubal ectopic pregnancy compared to those with a normal pregnancy [54].…”
Section: Adrenomedullinmentioning
confidence: 95%
“…Stimulating effects of ADM is blocked by the calcitonin-gene-related peptide (CGRP) receptor antagonist [53]. In line with these studies, it has been suggested that plasma and tubal levels of ADM are lower in patients with tubal ectopic pregnancy compared to those with a normal pregnancy [54].…”
Section: Adrenomedullinmentioning
confidence: 95%
“…Indeed, recent studies showed that plasma and oviductal tissue ADM levels in patients with tubal ectopic pregnancy are lower than those from patients with normal pregnancy. Importantly, both ciliary beat frequency and frequency of muscle contraction of oviducts from patients with tubal ectopic pregnancy were found to be significantly lower than those from normal pregnancy [157]. Therefore, a low ADM level in the oviduct may lead to the retention and implantation of embryos in the oviduct in tubal ectopic pregnancies as a result of decreased ciliary beating and muscle contraction.…”
Section: The Role Of Clr/ramp Receptor Signaling In the Oviductmentioning
confidence: 99%
“…Therefore, a low ADM level in the oviduct may lead to the retention and implantation of embryos in the oviduct in tubal ectopic pregnancies as a result of decreased ciliary beating and muscle contraction. Thus, the plasma ADM level may be a useful biomarker for the prediction of tubal ectopic pregnancy [157]. …”
Section: The Role Of Clr/ramp Receptor Signaling In the Oviductmentioning
confidence: 99%
“…Adrenomedullin is a peptide hormone belonging to calcitonin/calcitonin gene related peptide, and is thought be involved in endometrial angiogenesis. Liao et al found plasma and oviductal tissue adrenomedullin to be lower in EP and suggested that this decreases ciliary beating and muscle contraction leading to retained embryo and its implantation in the oviduct [99]. Similar findings were observed in nasal epithelium in patients of tEP by the same group [100].…”
Section: Adrenomedullinmentioning
confidence: 66%